The Bildung Theory. Wilhelm von Humboldt (Circa 1794) - Murillo, Fernando (Cuadernos de Historia, 2022)
The following text corresponds to a fragment written by Wilhelm von Humboldt between 1793 and 1794, and now translated for the first time into Spanish. It is a text that, despite its brevity, is of special importance for educational studies for at least three reasons. First, it is the first systematic approach to theorize the notion of Bildung (training) in specifically educational terms. Secondly, because it provides a clear and synthetic entry point to understand the anthropological assumptions and the impetus with which Humboldt understood education and its administration under his leadership as minister. Third, it provides a crucial background for tracing the intellectual history of education. It is from these three key elements that we can approach an understanding of Humboldt and his concept of education and recognize the traces of his influence that can be felt to this day both in Europe and in some countries of the Americas.